Infectious risk stratification in multiple sclerosis patients receiving immunotherapy. Issue 12 (24th November 2017) - Graf, Jonas; Leussink, Verena I.; Dehmel, Thomas; Ringelstein, Marius; Goebels, Norbert; Adams, Ortwin; MacKenzie, Colin R.; Warnke, Clemens; Feldt, Torsten; Lammerskitten, Anna; Klotz, Luisa; Meuth, Sven; et al.
Abstract: The increasing number of potent treatments for multiple sclerosis warrants screening for infections. To investigate the prevalence of infections in two independent German patient cohorts with multiple sclerosis/neuromyelitis optica spectrum disorders (NMOSD), we performed a retrospective chart review study of multiple sclerosis/NMOSD patients who underwent testing for infections between 2014 and 2016. We show that 6 out of 80 tested patients (Düsseldorf cohort) and 2 out of 97 tested patients (Münster cohort) had a latent tuberculosis infection; total 3.95%, 95% CI: 2–8%. Our findings suggest that latent tuberculosis infection is frequent (>1%). Screening should be performed before embarking on immunomodulatory therapies to allow treatment and mitigation of the risk of a reactivation.